Etos Kerja Perspektif Al-Qur’an dan Hadis - Khairullah; Aziz Taufiqurrahim; Eko Nur Rohman; Dhiah Rahmawati; Abdul Mufid (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Qur'an and Hadith are Islamic teachings in which there are teachings for charity and work which are prescribed in the sentence